2022
DOI: 10.3390/diagnostics12112715
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Photon Counting Detector CT Derived Virtual Monoenergetic Images on the Diagnosis of Pulmonary Embolism

Abstract: Purpose: To assess the impact of virtual-monoenergetic-image (VMI) energies on the diagnosis of pulmonary embolism (PE) in photon-counting-detector computed-tomography (PCD-CT). Methods: Eighty patients (median age 60.4 years) with suspected PE were retrospectively included. Scans were performed on PCD-CT in the multi-energy mode at 120 kV. VMIs from 40–70 keV in 10 keV intervals were reconstructed. CT-attenuation was measured in the pulmonary trunk and the main branches of the pulmonary artery. Signal-to-nois… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…In PCD-CT examinations of 80 patients with suspected pulmonary embolism (PE), subjective PE visibility was rated highest in VMIs at 50 keV. 64 For coronary CTA, VMIs at 40 keV were preferred when combined with high levels of iterative reconstruction (QIR 3 and QIR 4) both in a phantom evaluation and in a study of 10 patients. 65 Meanwhile, the possibility of contrast agent reduction when using VMIs at low energy has been investigated.…”
Section: Spectral Imaging Capabilitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In PCD-CT examinations of 80 patients with suspected pulmonary embolism (PE), subjective PE visibility was rated highest in VMIs at 50 keV. 64 For coronary CTA, VMIs at 40 keV were preferred when combined with high levels of iterative reconstruction (QIR 3 and QIR 4) both in a phantom evaluation and in a study of 10 patients. 65 Meanwhile, the possibility of contrast agent reduction when using VMIs at low energy has been investigated.…”
Section: Spectral Imaging Capabilitiesmentioning
confidence: 99%
“…In a comparative study of 39 patients undergoing contrast-enhanced abdominal PCD-CT in the portal-venous phase, 63 the authors found optimal results with standardized reconstructions of VMIs at 50 keV, which showed significantly higher CNR at the same radiation dose with similar subjective image quality compared with EID-CT. Figure 10 shows a clinical example of an abdominal CT scan. In PCD-CT examinations of 80 patients with suspected pulmonary embolism (PE), subjective PE visibility was rated highest in VMIs at 50 keV 64 . For coronary CTA, VMIs at 40 keV were preferred when combined with high levels of iterative reconstruction (QIR 3 and QIR 4) both in a phantom evaluation and in a study of 10 patients 65 …”
Section: Benefits Of Photon-counting Detector Ct and Their Clinical T...mentioning
confidence: 99%
“…Whether a previous measurement of the cardiovascular circulation time or a general increase in the delay between the contrast injection and the scan is the answer to this problem needs to be investigated. The noise level reduction in low keV VMIs on a PCD-CT compared to a EID-CT has been shown in multiple studies and examined body parts [22,30]. In addition, the rst studies have been published that combined increase of attenuation of low keV reconstructions with noise reduction on PCD-CT to reduce the amount of the iodine load.…”
Section: Discussionmentioning
confidence: 99%
“…As far as the authors are aware, as of the current date, only one investigation (Yalynska et al .) has been conducted on PCD-CT using different image reconstruction parameters, including a 2-mm slice thickness and keV values ranging from 40 to 70 keV [ 29 ]. Yalynska et al .…”
Section: Discussionmentioning
confidence: 99%